Inquiry Learning as a Manifestation of Hadith Reception on Questioning in Islamic Religious Education - Ela Nurlela; Inas Dhia Fauziah; Hikmal Alfiyansyah; Ahmad Nazar Fakhury; Maslani (Jurnal al-Thullab, 2026)
Islamic Religious Education often relies on a one way teaching pattern that significantly limits student participation and questioning, despite the Islamic scholarly tradition highly valuing questioning as mandated in the hadith of the Prophet Muhammad. Therefore, this study aims to describe the practice of inquiry learning in Islamic Religious Education and analyze these pedagogical practices as a practical reception of the hadith regarding questioning. Utilizing a qualitative field study design, data were collected through classroom observations and in-depth interviews with teachers, which were subsequently analyzed using a living hadith perspective. The findings reveal that inquiry learning serves as a transformative mechanism, shifting the hadith on questioning from a mere normative text into a tangible cultural behavior of dialectical questioning within the classroom. Teachers effectively act as mediators who enliven the hadith’s mandate by facilitating problem-based stimuli and dialogue spaces. As a contribution, this study offers a practical pedagogical model for educators to seamlessly integrate fundamental Islamic scholarly values into daily teaching. Furthermore, the findings imply a critical need for a paradigm shift in religious education methodology, moving from dogmatic-reproductive transmission toward an inquiry-based framework to foster a dynamic learning environment.